2001
DOI: 10.1006/jdeq.2001.3998
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Singularities for Fully Nonlinear Elliptic Equations

Abstract: We obtain Serrin type characterization of isolated singularities for solutions of fully nonlinear uniformly elliptic equations F(D 2 u)=0. The main result states that any solution to the equation in the punctured ball bounded from one side is either extendable to the solution in the entire ball or can be controlled near the centre of the ball by means of special fundamental solutions. In comparison with semi-and quasilinear results the proofs use the viscosity notion of generalised solution rather than distrib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 36 publications
(43 reference statements)
1
27
0
Order By: Relevance
“…If u is bounded above or below in a neighborhood of the origin, then precisely one of the following five alternatives holds: (i) the singularity is removable; that is, u can be defined at the origin so that This theorem generalizes a result of Labutin [17], who proved (i)-(iii) above under the supplementary assumptions that F is rotationally invariant and there exist (fundamental) solutions u and v of F .D 2 u/ D 0 in R n n f0g such that u.x/ ! 1 and v.x/ !…”
Section: F M / Wd F M /mentioning
confidence: 70%
See 3 more Smart Citations
“…If u is bounded above or below in a neighborhood of the origin, then precisely one of the following five alternatives holds: (i) the singularity is removable; that is, u can be defined at the origin so that This theorem generalizes a result of Labutin [17], who proved (i)-(iii) above under the supplementary assumptions that F is rotationally invariant and there exist (fundamental) solutions u and v of F .D 2 u/ D 0 in R n n f0g such that u.x/ ! 1 and v.x/ !…”
Section: F M / Wd F M /mentioning
confidence: 70%
“…For fully nonlinear operators this is not true, as noticed by Labutin [17], who showed that if ¤ ƒ, then P C ;ƒ . ƒ.n 1/= 1 / vanishes near the origin in a reasonable weak sense.…”
Section: F M / Wd F M /mentioning
confidence: 87%
See 2 more Smart Citations
“…See [18], [19] and [9] for further discussion on the fundamental solutions for the Pucci operators M In this section we provide a proof of Theorem 1.3, which is a consequence of a more general theorem that involves more general nonlinearities. But before going to that, we state a Comparison Principle due to Ishi and Lions [16], which will be used repeatedely in the proof of our results.…”
Section: Lemma 22 If F Is a Function Satisfying (F1) − (F3) Then Tmentioning
confidence: 99%